The impact of integrated technology on students' logical thought in mathematics: A case study of Kazakhstan - Ontuganova, Shynar; Zhumabayeva, Zhazira; Abilkhairova, Zhanar; Akzholova, Aktoty; Zhunusbekova, Aziza (Journal of Education and e-Learning Research, 2023)
This study aims to assess the impact of integrative technology on the improvement of the logical thinking of students in mathematics, their goals and the appropriate technological process. The study used mixed research methods. Participants included third-grade students attending elementary schools No. 12 and Ataturk in Kentau (Kazakhstan) during 2019-2022. The results indicated that primary school teachers do not pay attention to the improvement of the logical thinking of lower-grade students in mathematics. The research findings suggest that integrative technology improved logical thought in lower-grade students in the experimental group in mathematics. Finally, the study offers suggestions to improve the work of primary school teachers in developing the logical thinking of children in mathematics in Kazakhstan to increase the effectiveness of this process without increasing the burden on students or changing the curriculum.